Study of Fluid Flow Characteristics and Mechanical Properties of Aviation Fuel-Welded Pipelines via the Fluid–Solid Coupling Method - Changhong Guo; Mengran Di; Hanwen Gong; Jin Zhang; Shibo Sun; Kehua Ye; Bin Li; Lingxiao Quan (Aerospace)
The welded pipeline structure of aircraft fuel is a complex and diverse entity, significantly influenced by fluid–solid coupling. The refined aviation fuel-welded pipeline model plays a pivotal role in the investigation of its fluid–solid coupling mechanical properties. However, the mechanical analyses of pipelines with welded structures frequently simplify or ignore the influence of the weld zone (WZ). Consequently, these analyses fail to reveal the complex interactions between different weld zones in detail. In this study, a comprehensive and precise fuel-welded pipeline refinement model is developed through the acquisition of microstructural dimensions and mechanical parameters of the weld zone via metallographic inspection and microtensile testing. Additionally, the influence of clamps and brackets under airborne conditions is fully considered. Furthermore, the numerical simulation results are compared and verified using modal and random vibration tests. This paper addresses the impact of diverse fluid characteristics on the velocity field, pressure field, and stress in disparate areas, and it also conducts an investigation into the random vibration characteristics of the pipeline. The results demonstrate that the fluid pressure and velocity exert a considerable influence on the fluid flow state and structural stress distribution within the pipeline. An increase in flow velocity and alteration to the pipeline geometry will result in a change to the local velocity distribution, which in turn affects the distribution of the fluid pressure field. The highest stresses are observed in the weld zone, particularly at the junction between the weld zone and the heat-affected zone (HAZ). In contrast, the stresses in the bend region exhibit a corrugated distribution in both the axial and circumferential directions. An increase in fluid pressure has a significant impact on the natural frequency of the pipeline. This study enhances our comprehension of the mechanical properties of aircraft fuel lines with fluid–solid coupling and provides a foundation and guidance for the optimal design of fuel-welded lines.